Journalists’ Response and Reporting of Public Emergencies in the Era of Artificial Intelligence - Shaoying Lian; Ruoyu Mi; Runhua Tang (Applied Bionics and Biomechanics)
In order to improve the response ability of journalists to public emergencies, this study uses the computer simulation research method, based on Shannon’s information theory and the basic theory of journalism and communication, constructs the general model of public emergencies based on the statistical results of big data, and constructs the irrational natural person game model of four types of news communication participants. In the simulation analysis, it is found that in the face of public emergencies, journalists, on the one hand, firmly implement the publicity caliber, strengthen the amount of creation, and improve the forwarding amount and approval amount of manuscripts under the artificial intelligence news system. On the other hand, they should achieve effective interaction with nonofficial news media such as we media, and the subjective news department should provide effective guidance and guidance to the media.